Launch of IFPRI’s 2013 Global Food Policy Report - Fan, Shenggen (2014)
Launch of IFPRI’s 2013 Global Food Policy Report on March 12, 2014 at IFPRI by Shenggen Fan. Speakers: Shenggen Fan, Director General of IFPRI | Homi Kharas, Senior Fellow & Deputy Director for the Global Economy & Development Program, Brookings Institution | Asma Lateef, Director, Bread for the World Institute | Tjada McKenna, Deputy Coordinator for Development for Feed the Future and Acting Assistant to the Administrator at USAID’s Bureau for Food Security.